2012
DOI: 10.1097/mbc.0b013e32834fb599
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic ketoacidosis complicated by generalized venous thrombosis

Abstract: Venous thromboembolism is a rarely described complication of diabetic ketoacidosis (DKA). We describe a 21-year-old male patient with poorly controlled type 1 diabetes mellitus who was admitted with DKA, presumably secondary to noncompliance, whose clinical picture was complicated by generalized thrombosis involving multiple venous locations including renal vein, pulmonary vasculature, external iliac and common iliac veins. The patient had no family history of any coagulation disorders and a hypercoagulabilty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…More recently, Ozdemir et al reported a case of a 57-year-old woman who was admitted with DKA and a pulmonary embolus, successfully treated with tissue plasminogen activator and found to have elevated homocysteine concentrations (46). Cherian et al reported a case of a 21-year-old man with type 1 diabetes mellitus that developed multiple venous thromboses, including the renal vein, iliac veins and pulmonary vasculature, three days after admission for diabetic ketoacidosis due to non compliance with insulin therapy (31). A similar case of portal vein thrombosis in a patient with DKA was recently seen in our office.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Ozdemir et al reported a case of a 57-year-old woman who was admitted with DKA and a pulmonary embolus, successfully treated with tissue plasminogen activator and found to have elevated homocysteine concentrations (46). Cherian et al reported a case of a 21-year-old man with type 1 diabetes mellitus that developed multiple venous thromboses, including the renal vein, iliac veins and pulmonary vasculature, three days after admission for diabetic ketoacidosis due to non compliance with insulin therapy (31). A similar case of portal vein thrombosis in a patient with DKA was recently seen in our office.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet function has been shown to be abnormal in DM (29). Several reports have suggested that diabetes mellitus, and diabetic ketoacidosis in particular, represent a prothrombotic state (25,(30)(31)(32). Carl et al monitored the changes of protein C, protein S, von Willebrand factor (vWF), fibrinogen, homocysteine and folate in a group of young patients with DKA prior to, during, and following treatment (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…He developed multiple venous thromboses including renal, pulmonary, and iliac veins. ‘Hypercoaguability work‐up was negative.’ Forensic pathologists described seven cases of fatal massive pulmonary embolus in DKA. In four patients the diagnosis was made post‐mortem …”
Section: Diabetic Ketoacidosis and Hyperosmolar Hyperglycaemic Statementioning
confidence: 99%
“…Hematology workup showed no underlying hypercoagulability. Thus the DVT was considered as another complication of DKA [ 20 22 ].…”
Section: Case Presentationmentioning
confidence: 99%